Association between traumatic events and post-traumatic stress disorder: results from the ESEMeD-Spain study. (25th February 2014) - Olaya, B.; Alonso, J.; Atwoli, L.; Kessler, R. C.; Vilagut, G.; Haro, J. M.
Abstract : Background: The relative importance of traumatic events (TEs) in accounting for the social burden of post-traumatic stress disorder (PTSD) could vary according to cross-cultural factors. In that sense, no such studies have yet been conducted in the Spanish general population. The present study aims to determine the epidemiology of trauma and PTSD in a Spanish community sample using the randomly selected TEs method. Methods: The European Study of the Epidemiology of Mental Disorders (ESEMeD)-Spain is a cross-sectional household survey of a representative sample of adult population. Lifetime prevalence of self-reported TEs and lifetime and 12-month prevalence of PTSD were evaluated using the World Health Organization (WHO) Composite International Diagnostic Interview. Reports of PTSD associated with randomly selected TEs were weighted by the individual-level probabilities of TE selection to generate estimates of population-level PTSD risk associated with each TE. Results: Road accident was the most commonly self-reported TE (14.1%). Sexual assault had the highest conditional risk of PTSD (16.5%). The TEs that contributed most to societal PTSD burden were unexpected death of a loved one (36.4% of all cases) and sexual assault (17.2%). Being female and having a low educational level were associated with low risk of overall TE exposure and being previously married was related to higher risk. Being female was related to high risk of PTSD after experiencing a TE. Conclusions: Having an accident is commonly reported among Spanish adults, but two TE are responsible for the highest burden associated with PTSD: the unexpected death of someone close and sexual assault. These results can help designing public health interventions to reduce the societal PTSD burden.